The DNA of peace with a territorial focus in three municipalities of Magdalena (2020)
This work presents conceptual and reflection elements on the territorial approach, the perception on the peace agreements in the municipalities, the role and actions of the organizations in the territory as well as the component of associativity as an articulating and dynamic axis of individual projects and collective. The book takes as a base the results and the experience obtained in the research “Peace with a territorial and solidary approach: practices and community perceptions in three municipalities of Magdalena Medio. Supplies for a social agenda “, descriptive-interpretative study, oriented to identify the conceptions that, on Peace, Territory, armed conflict and collective life projects, communities have built in the municipalities of Barrancabermeja, San Pablo and Puerto Boyacá, as inputs important for the construction of intersectoral and regional agendas that strengthen the implementation of Peace agreements. Five techniques were applied (characterization, interview, focus group, cartography and map of actors) to a total of 66 participants, who represented 27 organizations. The results show the existence of an unfavorable perception regarding the territorial approach, given that this does not materialize in the communities, a rupture is perceived between what is proposed through normative frameworks and public policies with the way in which they operationalize, in addition to delegitimization and non-compliance of actions in the development plans; Likewise, organizations are conceived as spaces of citizen articulation that facilitate the construction of scenarios for psycho-social and political accompaniment and support, the restoration of the being and the social fabric, the planning and development of the territory, the defense and guarantee of rights. Peace is conceived as a fundamental right and social property, multicultural, with personal origin and interpersonal effects; new cycles of violence are identified, as well as dissatisfaction with minimum vitals. The findings are conceived as an important input for the generation of actions that allow the strengthening of the relations of the communities and the State, as well as the consolidation of Peace in the territories.